MANFAAT, PROSEDUR DAN KENDALA PENDAFTARAN HAK MILIK INTELEKTUAL - Sutri Helfianti; Iskandar Iskandar (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2018)
The benefit of registering Intellectual Property of an Brand IntellectualWork is essential to protect our creative assets. The indifference in themaintenance of Intellectual Property may lead to remorse especially when theBrand Work is becoming widely known, protecting the trademark of theIntellectual Property right from the acknowledgment of others. For theimplementation of registration of Intellectual Property, process / procedure isrequired, such as applying after completion of all required requirements. Inaddition to these conditions, which is not less important is that each registration ischarged differently depending on what he enrolled. The process / procedure is setin different laws and regulations depending on the registration of what you wantdone, eg Copyright, Brand and others. Obstacles encountered in the field, noregistration, especially patents, between the costs and benefits obtained lesscomparable. The relatively large cost is spent while the economic value obtainedis still small for now.